Specific MicroRNAs Differentiate Adrenocortical Adenomas from Carcinomas and Correlate With Weiss Histopathologic System. Issue 7 (August 2015) - Feinmesser, Meora; Benbassat, Carlos; Meiri, Eti; Benjamin, Hila; Lebanony, Danit; Lebenthal, Yael; de Vries, Liat; Drozd, Tamara; Spector, Yael
<x xml:space="preserve">Abstract</x> MicroRNAs (miRs) play a central role in regulating gene expression and are strongly associated with cancer development. This study sought to determine if adrenocortical carcinomas can be differentiated from adenomas by their miR profiles and to correlate the findings with the histologic Weiss system for identifying malignancy in adrenocortical tumors (ACTs). Forty-six primary and 2 recurrent ACTs retrieved from the files of the pathology department of a tertiary medical center were evaluated blindly for the Weiss criteria. High-quality RNA was extracted, and miR expression was evaluated with microarrays and quantitative reverse-transcriptase polymerase chain reaction. The Weiss system defined 17 tumors as carcinomas and 29 as adenomas. On microarray analysis, over a dozen miRs were upregulated or downregulated in carcinomas compared with adenomas. Upregulation of miR-503 was the best single discriminator of malignancy. The combination of miR-34a and miR-497 underexpression discriminated carcinomas from adenomas with 100% sensitivity and 96% specificity. Statistical analysis revealed a high level of correspondence between the Weiss system and miR expression. In conclusion, miR expression can accurately identify malignant ACTs with equal efficiency to the Weiss system. miR analysis may have added value in tumors with borderline features that are difficult to interpret histopathologically.